Model Epistemologi Personal dalam Keyakinan Tauhid Nabi Ibrahim As (Perspektif Psikologi dan Islam) - Ali Mahmud Ashshiddiqi (Psympathic : Jurnal Ilmiah Psikologi, 2017)
This library research explores the content of the Quran Surah Al An'am verses 74-79 and Surah Al Baqarah verse 131 about the monotheistic faith of the prophet Ibrahim. Based on the data of historical information and interpretation of Quran from the literature sources that collected through documentation, this study used historical, hermeneutics, and synthetic analysis approaches to uncover the model of personal epistemology from that monotheistic faith. Through descriptive-analytic, descriptive-comparative analyses and interpretation with the pattern of reflective thinking, the result indicates that the psycho-social and spiritual or religiosity conditions created an epistemic climate and encouraged epistemic changes on the prophet Ibrahim. The model of personal epistemology of the prophet Ibrahim accommodate existing models and different from the other models, especially with regard to the involvement of revelation and transcendental awareness factors and psychological qualities such as sincerity, love of truth, courage, and commitment to fight for conviction.